GRAIN TEMPERATURE CONTROL IN METAL SILOS WITH LONG-TERM STORAGE - СОКОЛОВСЬКА, ОЛЕНА; VALEVSKA, LIUDMYLA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The temperature of grain in storage is a complex process determined by the interaction of various factors. It is important to establish effective monitoring and management systems to ensure optimal storage conditions and avoid negative consequences such as spontaneous combustion or product spoilage. Grain temperature plays an important role in maintaining its quality during storage. Temperature control is a key element to avoid problems such as spontaneous combustion, fungal and bacterial growth, and to ensure optimal storage conditions. Grain thermometry is an important part of monitoring grain storage and processing conditions in elevators and warehouses. Temperature plays an important role in maintaining quality and avoiding problems such as self-ignition. Various factors can affect the change in grain temperature during storage: climatic conditions, grain moisture, location of thermometers, grain condition, storage period, seasonal changes, level of ventilation, etc. Proper management of these factors is important to maintain grain quality and prevent potential problems such as spontaneous combustion or mold growth. We conducted a study of temperature changes in the formed layers of grain during its storage in metal silos. The influence of natural conditions and the location of silos on the storage of grain was established and recommendations were given for its storage in metal silos. Special attention should be paid to the contact zones with the surface of the grain embankment and the zones adjacent to the walls of the slurry, they are the most sensitive to temperature changes. The air temperature in the silo affects the temperature of the upper layers of the grain mass, which are in direct contact with it. When the ambient temperature rises, the air temperature in the silo rises, because the metal surfaces of the silo have high thermal conductivity.